Numerical Analysis of The Multi-Stage Reverse Deep Drawing Process - Kariem Muhson Younis; Adil Shbeeb Jaber; Ammar Mahdi salah (Engineering and Technology Journal, 2016)
The paper presents an analysis of the multistage deep drawing process considering the three deformation stages namely drawing reverse and reverse redrawingrespectively. This work aim to study the mechanism of deformation during the redrawing process where the second and the third stages were done in reverse redrawing and study the effect of this mechanism on produced cup wall thickness, strain distribution across the wall of the drawn part. 2-D model of cylindrical cup (46.75mm) diameter has been developed in the first stage from sheet with thickness (0.5mm) of the low carbon steel (AISI 1008) and (85mm) diameter, while for second and third stages of drawing a punch diameter (32.725mm, 27.489mm) respectively, and inside diameter of dies equal to (33.825mm, 28.589mm) respectively, the clearance is chosen for three stage equal to 0.55mm. A commercial available finite element program code (ANSYS 11), is used to perform the numerical simulation of the multistage deep drawing. The results show that, when considering multi-stage drawing, the task is even more difficult because the strain and thickness distribution resulting from the first stage will influence the subsequent results,increase in thinning in the wall cup will appear in the second and third stages. Finally this work introduces new method (multi reverse redrawing) to produce circular cup throw three stages of drawing reduction in one stroke without the need to the loading and unloading the tools among the stages as in direct redrawing which means reducing the cost, time, efforts and enhancing cup production.